Анализ экспрессии генов целлюлозосинтезирующего комплекса и цитоскелетных белков в проростках льна (Linum usitatissimum L.) - Галиновский, Д.В.; Подвицкий, Т.А.; Баер, Г.Я.; Пирко, Я.В.; Анисимова, Н.В.; Хотылева, Л.В.; Емец, А.И.; Кильчевский, А.В.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. Study of gene expression involved in the correct orientation and deposition of cellulose fibrils in the stems of different genotypes of flax (Blakit and Ariane, Endress Olajlen and Dehiscens) differing in fiber quality is one of the considerable interest for researchers. Methods. The RT PCR and qPCR for gene expression analysis of cellulose synthase complex (Ces genes) and the cytoskeleton (actin and tubulin genes) in seedlings of flax were used. Results. The expression of genes LusСesA1, LusСesA4, LusСesA7, LusСesA9, Actin and Tubulin (TUA) in ten-days hypocotyls all of the studied varieties of flex were described. Conclusions. It was found that the key cellulose biosynthesis genes in hypocotyls of flax were LusCesA4 and LusCesA7 whose expression is 1–2 orders of magnitude higher than expression of CesA genes of other classes. In the varieties of flax, forming a high-quality fiber, the level of gene expression LusCesA4 and LusCesA7 were lower than that of flax Dehiscens. The level of gene expression of the cytoskeleton as a whole was higher than Ces genes in all the samples studied.